impact of hypoxia on bacterial infection - Schaffer, Kirsten; Taylor, Cormac T (The FEBS journal, 2015)
Tissue hypoxia is a common microenvironmental feature during inflammation associated with bacterial infection. Hypoxia has recently been shown to play an important role in both innate and adaptive host immunity through the regulation of transcription factors, including hypoxia‐inducible factor and nuclear factor‐κB, in both infiltrating immunocytes and inflamed resident cells. Recent studies have suggested that, by regulating these important immune effector pathways in host tissues, hypoxia can significantly alter the process of bacterial infection and subsequent disease progression. Although hypoxia is often beneficial in terms of reducing the development of infection, its net effect depends on a number of factors, including the nature of the pathogen and the characteristics of the infection encountered. In this minireview, we will discuss the impact of local tissue hypoxia and the resulting activation of hypoxia‐sensitive pathways on bacterial infection by a range of pathogens. Furthermore, we will review how this knowledge may be used to develop new approaches to anti‐infective therapeutics.